Enhancing water use efficiency in wheat : 40 Years of genetic gains in the Argentine Pampas - Curin, Facundo; Otegui, María Elena; Gonzalez, Fernanda Gabriela (Elsevier, 2025)
Understanding the impact of breeding on water use and productivity, particularly in underexplored environments where pre-anthesis rainfall is often limited, is crucial for increasing wheat grain yield (GY) under future climatic scenarios. The aim of this work was to study the effects of breeding on GY and its physiological determinants, including water use and water use efficiency among cultivars released to the Argentine market over a 40-year period. Ten Argentinean cultivars classified into early cycle (EC) and late cycle (LC), based on time to anthesis, were grown across three seasons (2015, 2016, and 2017) under irrigated, rainfed, and water restricted conditions. Breeding increased GY by enhancing the harvest index (HI) in LC cultivars and the total biomass (BT) in EC cultivars. These improvements were accompanied by increases in water use efficiency for grain yield production (WUEGY,ETc) of 1.11 % and 0.45 % per year among LC and EC cultivars, respectively, and a 0.29 % per year improvement in water use efficiency for biomass production (WUEBT,ETc) among EC cultivars. Crop evapotranspiration (ETC) decreased by 0.16 % per year exclusively in LC cultivars. Transpiration use efficiency (TE) improved by 0.55 % and 0.45 % per year for LC and EC cultivars, respectively, driven by increases in radiation use efficiency (RUE) of 0.46 % and 0.24 % per year. Notably, no changes in canopy conductance (gC) were observed. Finally, the proportion of water transpired before anthesis (pPREANT TC) decreased by 0.45 % per year in LC cultivars. The results of this study indicate that genetic improvement in Argentina has enhanced GY by increasing WUE and RUE, rather than total ETC. This is a particularly beneficial outcome for rainfed farming systems with limited water availability.